The correlation between serum alkaline phosphatase and grip strength in middle-aged and elderly people: NHANES 2011–2014 - Ziyi Zhang; Jiajie Zhou; Anpei Ma; Honggu Chen; Bo Wang; Guoyang Zhao (BMC Musculoskeletal Disorders)
Abstract Background Serum alkaline phosphatase (ALP) plays a crucial role in bone and muscle health. Previous studies have demonstrated that serum alkaline phosphatase (ALP) is closely associated with muscle mass. Nevertheless, the association between serum alkaline phosphatase (ALP) and grip strength remains unclear. Therefore, the present study focused on exploring the association of serum ALP with grip strength in middle-aged and elderly people. Methods We conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey conducted from 2011 to 2014. A total of 3514 participants (1891 males and 1623 females) aged 40–80 years were included in this study. Serum ALP and pelvic grip strength were analyzed as independent and dependent variables, additional variables were the possible impact modifiers. weighted generalized linear models and stratified analysis by gender, age group, and race were applied to assess the relationship between serum ALP and grip strength. Smooth curve fitting and threshold effect analysis/saturation effect analysis were used to analyze the nonlinear relationship between the 2 variables. Results In the gender-stratified subgroup analysis, we observed an inverse association between serum ALP and grip strength in both male and female. When stratified by age group, the association remained significant among participants 40–59 years of age, but not among those ≥ 60 years old. When stratified by race, the association remained significant among Non-Hispanic White and Non-Hispanic Black. It is noteworthy that serum ALP and grip strength showed a significant negative correlation among female aged 40–59 years, but not among female aged ≥ 60 years. Additionally, Smooth curve fitting showed that serum ALP had a nonlinear relationship with grip strength in male aged 40–59 years and male aged over 60 years, the inflection points are 54 IU and 97 IU respectively. Conclusion Our study revealed an inverse relationship between serum ALP and grip strength, this finding offers new insights and avenues for understanding how serum alkaline phosphatase affects skeletal muscle health.